1980
DOI: 10.1901/jeab.1980.33-59
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Timeout During Response Independent Food Schedules

Abstract: Rats' lever pressing terminated visual or auditory stimuli associated with fixed-time or variable-time schedules of food delivery and produced a timeout period during which food delivery could not occur. Lever pressing during a timeout period reinstated the food-associated stimuli and again permitted food delivery according to the fixed-time or variable-time schedules. The mean interfood interval ranged from 1 minute to 16 minutes (variable-time schedules) or 32 minutes (fixed-time schedules); the timer contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
3
8
0
1
Order By: Relevance
“…It has been suggested that this retreat from the area where reward occurs is maintained, in part, by the change in visual stimulation consequent to such behavior (Falk, 1977;Rand, 1977). This view is consistent with the fact that subjects that receive periodic reward will perform an operant response for contingent stimulus change during the period following reward delivery (time-out responding ;Brown & Flory, 1972;Lydersen, Perkins, Thome, & Lowman, 1980). In the present study, we investigated pigeons' spatial retreat from the reinforcer site following periodic grain presentations and examined its relation to operant time-out responding for stimulus change.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…It has been suggested that this retreat from the area where reward occurs is maintained, in part, by the change in visual stimulation consequent to such behavior (Falk, 1977;Rand, 1977). This view is consistent with the fact that subjects that receive periodic reward will perform an operant response for contingent stimulus change during the period following reward delivery (time-out responding ;Brown & Flory, 1972;Lydersen, Perkins, Thome, & Lowman, 1980). In the present study, we investigated pigeons' spatial retreat from the reinforcer site following periodic grain presentations and examined its relation to operant time-out responding for stimulus change.…”
mentioning
confidence: 68%
“…Previous parametric time-out studies in which a keypeck or barpress produced stimulus change found that the proportion of session time spent in the time-out condition is generally an increasing function of increasing the interreinforcer interval over a wide range of interval values (Falk, 1981;Lydersen et al, 1980), although there is some evidence (e.g., Brown & Flory, 1972) that it decreases at very long intervals. This increasing function has been viewed as reflecting an increasing aversiveness of the schedule as the interval is increased (Azrin, 1961;Falk, 1981).…”
mentioning
confidence: 99%
“…Specifically, there is an ‘engage’ drive, where behavior is maintained by the positively-reinforcing effects of the delivered stimulus (e.g., food) and an opposing ‘escape’ drive where behavior is governed by the delay of reinforcement within interval schedules. In general, as the FT interval between food reinforcement increases, behavior directed at obtaining the reinforcer declines (Herrnstein, 1970) and behavior directed at escaping the schedule escalates (Lydersen et al, 1980). Hypothetically, the interval at which these two oppositional forces on behavior are equal (i.e., intersect) is the interval of greatest ‘conflict’ in which the animal must reconcile the equal and opposing drives of whether to escape or to remain engaged.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also reveal a bitonic function, but with maximum rate of aggression occurring at relatively low reinforcement rates (about 20 to 60 reinforcements/h). Finally, there is some evidence of a bitonic relationship between reinforcement rate and rate of schedule-induced escape (Brown & Flory, 1972;Lydersen, Perkins, Thome, & Lowman, 1980), with maximum rate of induced escape occurring at even lower reinforcement rates (about 15 reinforcements/h or less).…”
Section: Other Obsenationsmentioning
confidence: 99%